IMPLEMENTASI DEEP LEARNING DALAM MEWUJUDKAN 7 KEBIASAAN ANAK INDONESIA HEBAT DI SEKOLAH MENENGAH KEJURUAN NEGERI TUTUR - Putri Nur Syifah; M. Jamhuri (STKIP Subang, 2026)
This study aims to analyze the implementation of deep learning in Islamic Religious Education (PAI) learning in realizing the 7 Habits of Great Indonesian Children at SMK Negeri Tutur. The research questions are: (1) how is the process of implementing deep learning in PAI learning at SMK Negeri Tutur, and (2) what is the implication of this implementation on the formation of the 7 Habits of Great Indonesian Children. This study uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, open questionnaires, observation, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The results show that PAI learning at SMK Negeri Tutur has shifted from a lecture- and memorization-based approach toward a more reflective, contextual, and meaningful learning process, marked by curriculum coordination, the redesign of lesson plans, and the use of discussion, case analysis, and digital media. This implementation also contributes positively to the formation of the 7 Habits, particularly in worship discipline, social care, and health awareness, although the achievement is not yet evenly distributed among students. These findings indicate that integrating deep learning into PAI curriculum is a strategic step in supporting students' holistic character development in vocational education.